Associations of childhood adiposity with adult intima–media thickness and inflammation: a 20-year longitudinal population-based cohort. Issue 3 (22nd March 2023) - Fujikawa, Tomona; Kobayashi, Masatake; Wagner, Sandra; Duarte, Kevin; Scherdel, Pauline; Heude, Barbara; Dupont, Vincent; Bozec, Erwan; Bresso, Emmanuel; Zannad, Faiez; Rossignol, Patrick; Girerd, Nicolas
Abstract : Background: The associations between childhood adiposity and adult increased carotid intima–media thickness (cIMT) have been well established, which might be corroborated by the association between adiposity in children and inflammation in adults. However, longitudinal data regarding biological pathways associated with childhood adiposity are lacking. Methods: The current study included participants from the STANISLAS cohort who had adiposity measurements at age 5–18 years [ N = 519, mean (SD) age, 13.0 (2.9) years; 46.4% male], and who were measured with cIMT, vascular-related and metabolic-related proteins at a median follow-up of 19 ± 2 years. BMI, waist-to-height ratio and waist circumference were converted to age-specific and sex-specific z -scores. Results: A minority of children were overweight/obese (16.2% overweight-BMI z -score >1; 1.3% obesity- z -score >2). Higher BMI, waist–height ratio and waist circumference in children were significantly associated with greater adult cIMT in univariable analysis, although not after adjusting for C-reactive protein. These associations were more pronounced in those with consistently high adiposity status from childhood to middle adulthood. Participants with higher adiposity during childhood (BMI or waist–height ratio) had higher levels of insulin-like growth factor-binding protein-1, protein-2, matrix metalloproteinase-3, osteopontin, hemoglobin and C-reactive protein in adulthood. Network analysis showed that IL-6, insulin-like growth factor-1 and fibronectin were the key proteins associated with childhood adiposity. Conclusion: In a population-based cohort followed for 20 years, higher BMI or waist-to-height ratio in childhood was significantly associated with greater cIMT and enhanced levels of proteins reflective of inflammation, supporting the importance of inflammation as progressive atherosclerosis in childhood adiposity. Abstract :